A Decision Model for Berth Allocation Under Uncertainty Considering Service Level Using an Adaptive Differential Evolution Algorithm - Liu, Changchun (WORLD SCIENTIFIC PUBL CO PTE LTD, 2019)
10.1142/S0217595916500494